22q11.2 Low Copy Repeats Expanded in the Human Lineage - Vervoort, Lisanne; Dierckxsens, Nicolas; Pereboom, Zjef; Capozzi, Oronzo; Rocchi, Mariano; Shaikh, Tamim H.; Vermeesch, Joris R. (Frontiers in Genetics, 2021)
Segmental duplications or low copy repeats (LCRs) constitute duplicated regions interspersed in the human genome, currently neglected in standard analyses due to their extreme complexity. Recent functional studies have indicated the potential of genes within LCRs in synaptogenesis, neuronal migration, and neocortical expansion in the human lineage. One of the regions with the highest proportion of duplicated sequence is the 22q11.2 locus, carrying eight LCRs (LCR22-A until LCR22-H), and rearrangements between them cause the 22q11.2 deletion syndrome. The LCR22-A block was recently reported to be hypervariable in the human population. It remains unknown whether this variability also exists in non-human primates, since research is strongly hampered by the presence of sequence gaps in the human and non-human primate reference genomes. To chart the LCR22 haplotypes and the associated inter- and intra-species variability, we de novo assembled the region in non-human primates by a combination of optical mapping techniques. A minimal and likely ancient haplotype is present in the chimpanzee, bonobo, and rhesus monkey without intra-species variation. In addition, the optical maps identified assembly errors and closed gaps in the orthologous chromosome 22 reference sequences. These findings indicate the LCR22 expansion to be unique to the human population, which might indicate involvement of the region in human evolution and adaptation. Those maps will enable LCR22-specific functional studies and investigate potential associations with the phenotypic variability in the 22q11.2 deletion syndrome.